Аналитическое определение сопротивления качения литейной формы по роликовым опорам - Анофриев, Павел Григорьевич; Бондаренко, Леонид Николаевич; Черкудинов, Владимир Эдуардович (НТУ "ХПИ", 2016)
На основе современных положений трибологии рассмотрена задача упругого контакта опорных роликов цилиндрической формы с опорным поясом формы центробежной литейной машины. Уточнены коэффициенты трения качения формы со стальными опорными поясами по роликам, изготовленным из низкомодульных материалов, таких как литейная сталь, бронза и латунь. Получены графики зависимости относительной деформации и допускаемых по условиям контактной прочности радиусов роликов в зависимости от модуля упругости их материала. Получены приведенные коэффициенты трения подшипников качения в зависимости от типа (шариковый, роликовый) и вращающегося внутреннего или наружного колец.

During the research, it is assumed to obtain analytical dependence for determining the rolling resistance of the steel belt supporting the mold on rollers, made of flowable materials. Compare values of coefficients of friction in the bearings of the rollers, the analytical method with the values proposed in the scientific and technical literature for designers and builders. Based on current provisions of tribology deals with the problem of elastic contact of rollers of cylindrical form with a support belt forms a centrifugal casting machine. Coefficients of rolling friction of the shaped steel support belts on rollers, made of flowable materials such as cast steel, bronze and brass. The obtained graphs of the relative deformation and permitted under the terms of the co ntact strength of the radii of the rollers according to the elastic modulus of their material. The reduced friction coefficients of rolling bearings depending on the type (ball, roller) and a rotating inner or outer ring. When rotating the outer ring of the bearing , the coefficient of rolling friction is higher by 14 to 27% than the rotation of the inner ring. Theoretically, from the condition of multiplicity of operating on the local contact deformation of the reference tire and roller every second car repair will be accompanied by a simultaneous replacement of worn equally reference tire and roller.
Analytical determination of the resistance of rolling the mold on the roller supports
Keywords: подшипник; ролик; контактные деформации; модуль упругости; коэффициент трения качения; bearing; roller; contact deformation; elastic modulus; rolling resistance